A spider silk-loaded sulfide hollow nanotube composite material and its preparation method and application
By growing CdS or supported NiS in situ on spider silk, a spider silk-loaded sulfide hollow nanotube composite material was prepared, which solved the agglomeration and photocorrosion problems of existing sulfide materials in the field of photocatalysis, and achieved efficient photocatalysis and easy recovery effects.
Patent Information
- Application Number
- CN202310458922.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-04-26
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2043-04-26
AI Technical Summary
The existing sulfide materials have problems such as the agglomeration and photocorrosion of nanoparticles in the field of photocatalytics, which limit their industrial applications.
Spider silk-loaded sulfide hollow nanotube composites are prepared by growing CdS or loaded NiS on spider silk, and the growth and dispersion of nanoparticles are controlled using the fishing web structure and silk protein characteristics of spider silk.
It effectively prevents the recombination of photogenerated electrons and holes, improves photocatalytic efficiency, and is easy to recover, suitable for industrial production.
Smart Images

Figure CN116440958B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of materials and relates to a nano material, in particular to a spider silk loaded sulfide hollow nano tube composite material and a preparation method and application thereof. Background Art
[0002] In recent years, the economy has developed rapidly, petrochemical energy has become increasingly depleted, and environmental pollution has become more and more serious. Therefore, seeking clean and efficient new energy has become the research direction of many scientists. Hydrogen energy has been a popular new energy in recent years, and people are also exploring its preparation methods. Among them, the use of photocatalysts to prepare hydrogen is a more effective method. Therefore, photocatalysts have become a hot topic of research, providing new ideas and directions for solving the two major problems of energy and environment currently faced by mankind. As a key substance for completing the utilization and conversion of solar energy, photocatalysts have become the research focus of photocatalytic technology. Sulfide semiconductor materials have attracted much attention in the field of photocatalysis due to their suitable energy band width and good light response range. However, when sulfide materials such as CdS are used alone as photocatalysts, there are problems such as easy agglomeration of nanoparticles and easy photocorrosion, which limits their industrial application. In order to solve these problems, sulfide materials are usually modified by methods such as doping elements, semiconductor composites and surface deposition of precious metals. Different semiconductors will form a heterojunction after composite, and the potential difference at the heterojunction interface can well change the movement path of photogenerated electron holes, thereby improving its photocatalytic efficiency. However, at present, such materials are limited, and there is an urgent need for a new sulfide composite material for use in fields such as photocatalysis. Summary of the invention
[0003] In view of the defects of the prior art, the present invention provides a spider silk loaded sulfide hollow nanotube composite material and its preparation method and application. Compared with a single material, the composite material effectively prevents the recombination of photogenerated electrons and holes, improves its photocatalytic efficiency and has the characteristics of easy recycling.
[0004] To achieve the above-mentioned purpose, the present invention provides a spider silk-loaded sulfide hollow nanotube composite material, which has the following characteristics: it is a spider silk-loaded CdS nanocomposite material with a nanotubular structure obtained by in-situ growing CdS on spider silk; or, it is a spider silk-loaded CdS / NiS nanocomposite material with a nanotubular structure obtained by in-situ growing CdS on spider silk and then loading NiS.
[0005] Furthermore, the present invention provides a spider silk-loaded sulfide hollow nanotube composite material, which may also have the following characteristics: wherein, a method for in-situ growing CdS on spider silk is: adding an aqueous solution of cadmium acetate and thiourea to a spider silk solution, and heating to in-situ grow CdS on the spider silk; a method for in-situ growing CdS on spider silk and then loading NiS is: dispersing spider silk loaded with CdS into an aqueous solution of nickel acetate and thiourea, and heating to load NiS.
[0006] The present invention also provides a method for preparing the spider silk-loaded sulfide hollow nanotube composite material, which has the following characteristics: the method for preparing the spider silk-loaded CdS nanocomposite material comprises the following steps: S1.1, dissolving cadmium acetate and thiourea in deionized water and ultrasonicating the solution to completely dissolve the sulfide; S1.2, adding spider silk solution to the solution obtained in S1.1, and ultrasonically oscillating; S1.3, transferring the solution obtained in S1.2 into a polytetrafluoroethylene reactor and heating for reaction, and after the reaction is completed, centrifuging, washing, and drying the solution to obtain the spider silk-loaded CdS nanocomposite material;
[0007] The preparation method of the spider silk loaded CdS / NiS nanocomposite material comprises the following steps: S2.1, dissolving cadmium acetate and thiourea in deionized water and ultrasonicating the solution to completely dissolve the sulfide; S2.2, adding spider silk solution to the solution obtained in S2.1 and ultrasonically oscillating; S2.3, transferring the solution obtained in S2.2 into a polytetrafluoroethylene reactor for heating and reaction, and after the reaction, centrifuging, washing and drying the solution to obtain spider silk loaded CdS hollow nanotubes; S2.4, uniformly dispersing the spider silk loaded CdS hollow nanotubes obtained in S2.3 into an aqueous solution of nickel acetate and thiourea, and then transferring the solution into a polytetrafluoroethylene reactor for heating and reaction, and after the reaction, centrifuging, washing and drying the solution to obtain the spider silk loaded CdS / NiS nanocomposite material.
[0008] Furthermore, the present invention provides a method for preparing a spider silk-loaded sulfide hollow nanotube composite material, which may also have the following characteristics: wherein, in S1.1 and S2.1, the mass ratio of cadmium acetate to thiourea is 0.234:0.152-0.182.
[0009] Furthermore, the present invention provides a method for preparing a spider silk-loaded sulfide hollow nanotube composite material, which may also have the following characteristics: wherein, in S1.2 and S2.2, the spider silk solution is prepared by dissolving the spider silk in an organic solution and adjusting the pH of the solution to 5 to 9.
[0010] Furthermore, the present invention provides a method for preparing a spider silk-loaded sulfide hollow nanotube composite material, which may also have the following characteristics: wherein the specific configuration method of the spider silk solution is: dispersing the spider silk in N-methylpyrrolidone or dimethyl sulfoxide, controlling the temperature to 160-180°C, stirring for 24 hours, and then filtering with a 400-mesh sieve, adjusting the pH of the solution to 5-9, to obtain a spider silk solution.
[0011] Furthermore, the present invention provides a method for preparing a spider silk-loaded sulfide hollow nanotube composite material, which may also have the following characteristics: wherein, in S1.3 and S2.3, the heating temperature is 150-200° C., and the heating time is 24 hours.
[0012] Furthermore, the present invention provides a method for preparing a spider silk-loaded sulfide hollow nanotube composite material, which may also have the following characteristics: wherein, in S2.4, the mass ratio of nickel acetate to thiourea is 0.015-0.088: 0.018-0.076.
[0013] Furthermore, the present invention provides a method for preparing a spider silk-loaded sulfide hollow nanotube composite material, which may also have the following characteristics: wherein, in S2.4, the heating temperature is 70-90° C. and the heating time is 12 hours.
[0014] The present invention also provides the application of the spider silk-loaded sulfide hollow nanotube composite material for photocatalytic degradation of water pollution, photoelectrolysis of water to produce hydrogen, reduction of carbon dioxide and the field of photoelectric devices.
[0015] The beneficial effects of the present invention are as follows: the present invention provides a spider silk-loaded sulfide hollow nanotube composite material and a preparation method thereof, which can be applied to the fields of photocatalytic degradation of water pollution, photoelectrolysis of water to produce hydrogen, reduction of carbon dioxide, and photoelectric devices. This nanomaterial is loaded with CdS or loaded with CdS and then loaded with NiS by in-situ growth on spider silk to obtain a spider silk-loaded CdS nanocomposite material or a spider silk-loaded CdS / NiS nanocomposite material. Compared with other polymer fibers, spider silk has unique advantages. Because when spider silk is used as a substrate to grow CdS nanoparticles in situ, the N and O atoms in the fishnet silk protein react with Cd 2+The gravitational force makes the generated CdS nanoparticles closely attached to the spider silk. This loading process can not only promote the close contact between spider silk and binary metal sulfide, but also control the growth direction of binary metal sulfide, and regulate the geometric morphology and dispersity of metal sulfide grains, broaden the spectral response range, promote the separation of electrons and holes, and achieve the goal of efficient and stable photocatalytic performance of binary metal sulfide. In addition, spider silk has the characteristic of easy sedimentation, so that the product has the characteristic of easy recycling. The preparation method of the spider silk loaded sulfide hollow nanotube composite material of the present invention is simple to operate, and the nanometer size, morphology, atomic ratio, etc. of the product are controllable, which is suitable for industrial production. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] Figure 1 is a scanning electron microscope (SEM) image of the spider silk-loaded CdS nanocomposite material of Example 1;
[0017] Figure 2 is a transmission electron microscope (TEM) image of the spider silk-loaded CdS nanocomposite material of Example 1;
[0018] Figure 3 is a scanning electron microscope (SEM) image of the spider silk-loaded CdS / NiS nanocomposite material of Example 7;
[0019] Figure 4 is a transmission electron microscope (TEM) image of the spider silk-loaded CdS / NiS nanocomposite material of Example 7;
[0020] Figure 5 is the XRD data of the spider silk-loaded CdS / NiS nanocomposite material of Example 7;
[0021] Figure 6 is the ultraviolet absorption spectrum of the spider silk-loaded CdS nanocomposite material degrading rhodamine B in Example 1;
[0022] Figure 7 is the photocurrent data of spider silk-loaded CdS / NiS nanocomposites of Examples 5 and 7;
[0023] Figure 8 These are the data for producing hydrogen from water by photocatalytic decomposition of spider silk-loaded CdS / NiS nanocomposites of Examples 5 to 8. DETAILED DESCRIPTION
[0024] The present invention is further described below in conjunction with specific embodiments.
[0025] Example 1
[0026] This embodiment provides a spider silk loaded CdS nanocomposite material, and the preparation method thereof comprises the following steps:
[0027] S1.1. Weigh 0.234 g of cadmium acetate and 0.182 g of thiourea, dissolve them in 30 ml of deionized water and sonicate the solution for 20 to 25 min to completely dissolve the sulfide;
[0028] S1.2, then add 20 ml of spider silk solution to the solution obtained in S1.1 and ultrasonically vibrate for 10 minutes;
[0029] The spider silk solution was prepared by dispersing 5 g of spider silk in 150 ml of N-methylpyrrolidone, controlling the temperature to 160° C., magnetically stirring for 24 h, then filtering with a 400-mesh sieve, and adjusting the pH of the solution to 5 to obtain a spider silk solution.
[0030] S1.3, the solution obtained in S1.2 was transferred into a polytetrafluoroethylene reactor and reacted at 160°C for 24 hours. After the reaction, the solution was centrifuged, washed and dried to obtain a spider silk-loaded CdS nanocomposite material, the SEM and TEM images of which are shown in FIG. Figure 1 and 2 shown.
[0031] Example 2
[0032] This embodiment provides a spider silk loaded CdS nanocomposite material, and the preparation method thereof comprises the following steps:
[0033] S1.1. Weigh 0.234 g of cadmium acetate and 0.182 g of thiourea, dissolve them in 30 ml of deionized water and sonicate the solution for 20 to 25 min to completely dissolve the sulfide;
[0034] S1.2, then add 20 ml of spider silk solution to the solution obtained in S1.1 and ultrasonically vibrate for 10 minutes;
[0035] The spider silk solution was prepared by dispersing 5 g of spider silk in 150 ml of N-methylpyrrolidone, controlling the temperature to 160° C., magnetically stirring for 24 h, then filtering with a 400-mesh sieve, and adjusting the pH of the solution to 5 to obtain a spider silk solution.
[0036] S1.3. Transfer the solution obtained in S1.2 into a polytetrafluoroethylene reactor and react at 180°C for 24 hours. After the reaction, centrifuge, wash and dry the solution to obtain spider silk-loaded CdS nanocomposite material.
[0037] Example 3
[0038] This embodiment provides a spider silk loaded CdS nanocomposite material, and the preparation method thereof comprises the following steps:
[0039] S1.1. Weigh 0.234 g of cadmium acetate and 0.182 g of thiourea, dissolve them in 30 ml of deionized water and sonicate the solution for 20 to 25 min to completely dissolve the sulfide;
[0040] S1.2, then add 20 ml of spider silk solution to the solution obtained in S1.1 and ultrasonically vibrate for 10 minutes;
[0041] The spider silk solution is prepared by dispersing 10 g of spider silk in 150 ml of dimethyl sulfoxide, controlling the temperature to 180° C., magnetically stirring for 24 hours, then filtering with a 400-mesh sieve, and adjusting the pH of the solution to 9 to obtain a spider silk solution;
[0042] S1.3. Transfer the solution obtained in S1.2 into a polytetrafluoroethylene reactor and react at 200°C for 24 hours. After the reaction, centrifuge, wash and dry the solution to obtain spider silk-loaded CdS nanocomposite material.
[0043] Example 4
[0044] This embodiment provides a spider silk loaded CdS nanocomposite material, and the preparation method thereof comprises the following steps:
[0045] S1.1. Weigh 0.234 g of cadmium acetate and 0.182 g of thiourea, dissolve them in 30 ml of deionized water and sonicate the solution for 20 to 25 min to completely dissolve the sulfide;
[0046] S1.2, then add 20 ml of spider silk solution to the solution obtained in S1.1 and ultrasonically vibrate for 10 minutes;
[0047] The spider silk solution is prepared by dispersing 10 g of spider silk in 150 ml of dimethyl sulfoxide, controlling the temperature to 180° C., magnetically stirring for 24 hours, then filtering with a 400-mesh sieve, and adjusting the pH of the solution to 9 to obtain a spider silk solution;
[0048] S1.3. Transfer the solution obtained in S1.2 into a polytetrafluoroethylene reactor and react at 150°C for 24 hours. After the reaction, centrifuge, wash and dry the solution to obtain spider silk-loaded CdS nanocomposite material.
[0049] Example 5
[0050] This embodiment provides a spider silk-loaded CdS / NiS nanocomposite material, the preparation method of which comprises the following steps:
[0051] S2.1. Weigh 0.234 g of cadmium acetate and 0.152 g of thiourea, dissolve them in 30 ml of deionized water and sonicate the solution for 20 to 25 min to completely dissolve them.
[0052] S2.2, then add 20 ml of spider silk solution to the solution obtained in S2.1, and ultrasonically vibrate for 10 min;
[0053] The spider silk solution was prepared by dispersing 5 g of spider silk in 150 ml of N-methylpyrrolidone, controlling the temperature to 160° C., magnetically stirring for 24 h, then filtering with a 400-mesh sieve, and adjusting the pH of the solution to 5 to obtain a spider silk solution.
[0054] S2.3, the solution obtained in S2.2 was transferred into a polytetrafluoroethylene reactor, and reacted at 150°C for 24 hours. After the reaction, the solution was centrifuged, washed, and dried to obtain an intermediate product - spider silk-loaded CdS hollow nanotubes;
[0055] S2.4. Evenly disperse the intermediate product obtained in S2.3 into an aqueous solution containing 0.0295 g nickel acetate and 0.026 g thiourea. Then transfer the solution into a polytetrafluoroethylene reactor and react at 90°C for 12 h. After the reaction, centrifuge, wash and dry the solution to obtain the target product - spider silk-loaded CdS / NiS nanocomposite material.
[0056] Example 6
[0057] This embodiment provides a spider silk-loaded CdS / NiS nanocomposite material, the preparation method of which comprises the following steps:
[0058] S2.1. Weigh 0.234 g of cadmium acetate and 0.152 g of thiourea, dissolve them in 30 ml of deionized water and sonicate the solution for 20 to 25 min to completely dissolve them.
[0059] S2.2, then add 20 ml of spider silk solution to the solution obtained in S2.1, and ultrasonically vibrate for 10 min;
[0060] The spider silk solution was prepared by dispersing 5 g of spider silk in 150 ml of N-methylpyrrolidone, controlling the temperature to 160° C., magnetically stirring for 24 h, then filtering with a 400-mesh sieve, and adjusting the pH of the solution to 5 to obtain a spider silk solution.
[0061] S2.3, the solution obtained in S2.2 was transferred into a polytetrafluoroethylene reactor, and reacted at 180°C for 24 hours. After the reaction, the solution was centrifuged, washed, and dried to obtain an intermediate product - spider silk-loaded CdS hollow nanotubes;
[0062] S2.4. Evenly disperse the intermediate product obtained in S2.3 into an aqueous solution containing 0.088 g nickel acetate and 0.076 g thiourea. Then transfer the solution into a polytetrafluoroethylene reactor and react at 70°C for 12 h. After the reaction, centrifuge, wash and dry the solution to obtain the target product - spider silk-loaded CdS / NiS nanocomposite material.
[0063] Example 7
[0064] This embodiment provides a spider silk-loaded CdS / NiS nanocomposite material, the preparation method of which comprises the following steps:
[0065] S2.1. Weigh 0.234 g of cadmium acetate and 0.152 g of thiourea, dissolve them in 30 ml of deionized water and sonicate the solution for 20 to 25 min to completely dissolve them.
[0066] S2.2, then add 20 ml of spider silk solution to the solution obtained in S2.1, and ultrasonically vibrate for 10 min;
[0067] The spider silk solution was prepared by dispersing 5 g of spider silk in 150 ml of N-methylpyrrolidone, controlling the temperature to 160° C., magnetically stirring for 24 h, then filtering with a 400-mesh sieve, and adjusting the pH of the solution to 5 to obtain a spider silk solution.
[0068] S2.3, the solution obtained in S2.2 was transferred into a polytetrafluoroethylene reactor, and reacted at 150°C for 24 hours. After the reaction, the solution was centrifuged, washed, and dried to obtain an intermediate product - spider silk-loaded CdS hollow nanotubes;
[0069] S2.4, the intermediate product obtained in S2.3 was uniformly dispersed in an aqueous solution containing 0.0358g nickel acetate and 0.031g thiourea, and then the solution was transferred into a polytetrafluoroethylene reactor and reacted at 70°C for 12h. After the reaction, the solution was centrifuged, washed and dried to obtain the target product - spider silk loaded CdS / NiS nanocomposite material, whose SEM, TEM and XRD images are shown as follows: Figure 3 , 4 and 5.
[0070] Example 8
[0071] This embodiment provides a spider silk-loaded CdS / NiS nanocomposite material, the preparation method of which comprises the following steps:
[0072] S2.1. Weigh 0.234 g of cadmium acetate and 0.152 g of thiourea, dissolve them in 30 ml of deionized water and sonicate the solution for 20 to 25 min to completely dissolve them.
[0073] S2.2, then add 20 ml of spider silk solution to the solution obtained in S2.1, and ultrasonically vibrate for 10 min;
[0074] The spider silk solution was prepared by dispersing 5 g of spider silk in 150 ml of N-methylpyrrolidone, controlling the temperature to 160° C., magnetically stirring for 24 h, then filtering with a 400-mesh sieve, and adjusting the pH of the solution to 5 to obtain a spider silk solution.
[0075] S2.3, the solution obtained in S2.2 was transferred into a polytetrafluoroethylene reactor, and reacted at 200°C for 24 hours. After the reaction, the solution was centrifuged, washed, and dried to obtain an intermediate product - spider silk-loaded CdS hollow nanotubes;
[0076] S2.4. Evenly disperse the intermediate product obtained in S2.3 into an aqueous solution containing 0.0358 g nickel acetate and 0.062 g thiourea. Then transfer the solution into a polytetrafluoroethylene reactor and react at 70°C for 12 h. After the reaction, centrifuge, wash and dry the solution to obtain the target product - spider silk-loaded CdS / NiS nanocomposite material.
[0077] Example 9
[0078] This embodiment provides a spider silk-loaded CdS / NiS nanocomposite material, the preparation method of which comprises the following steps:
[0079] S2.1. Weigh 0.234 g of cadmium acetate and 0.152 g of thiourea, dissolve them in 30 ml of deionized water and sonicate the solution for 20 to 25 min to completely dissolve them.
[0080] S2.2, then add 20 ml of spider silk solution to the solution obtained in S2.1, and ultrasonically vibrate for 10 min;
[0081] The spider silk solution is prepared by dispersing 10 g of spider silk in 150 ml of dimethyl sulfoxide, controlling the temperature to 180° C., magnetically stirring for 24 hours, then filtering with a 400-mesh sieve, and adjusting the pH of the solution to 9 to obtain a spider silk solution;
[0082] S2.3, the solution obtained in S2.2 was transferred into a polytetrafluoroethylene reactor, and reacted at 200°C for 24 hours. After the reaction, the solution was centrifuged, washed, and dried to obtain an intermediate product - spider silk-loaded CdS hollow nanotubes;
[0083] S2.4. Evenly disperse the intermediate product obtained in S2.3 into an aqueous solution containing 0.015 g nickel acetate and 0.018 g thiourea. Then transfer the solution into a polytetrafluoroethylene reactor and react at 70°C for 12 h. After the reaction, centrifuge, wash and dry the solution to obtain the target product - spider silk-loaded CdS / NiS nanocomposite material.
[0084] Example 10
[0085] This embodiment provides a spider silk-loaded CdS / NiS nanocomposite material, the preparation method of which comprises the following steps:
[0086] S2.1. Weigh 0.234 g of cadmium acetate and 0.152 g of thiourea, dissolve them in 30 ml of deionized water and sonicate the solution for 20 to 25 min to completely dissolve them.
[0087] S2.2, then add 20 ml of spider silk solution to the solution obtained in S2.1, and ultrasonically vibrate for 10 min;
[0088] The spider silk solution is prepared by dispersing 10 g of spider silk in 150 ml of dimethyl sulfoxide, controlling the temperature to 180° C., magnetically stirring for 24 hours, then filtering with a 400-mesh sieve, and adjusting the pH of the solution to 9 to obtain a spider silk solution;
[0089] S2.3, the solution obtained in S2.2 was transferred into a polytetrafluoroethylene reactor, and reacted at 200°C for 24 hours. After the reaction, the solution was centrifuged, washed, and dried to obtain an intermediate product - spider silk-loaded CdS hollow nanotubes;
[0090] S2.4. Evenly disperse the intermediate product obtained in S2.3 into an aqueous solution containing 0.015 g nickel acetate and 0.033 g thiourea. Then transfer the solution into a polytetrafluoroethylene reactor and react at 70°C for 12 h. After the reaction, centrifuge, wash and dry the solution to obtain the target product - spider silk-loaded CdS / NiS nanocomposite material.
[0091] The spider silk loaded CdS nanocomposites prepared in Examples 1 to 4 and the spider silk loaded CdS / NiS nanocomposites prepared in Examples 5 to 10 can be applied to the fields of photocatalytic degradation of water pollution, photoelectrolysis of water to produce hydrogen, reduction of carbon dioxide, preparation of photoelectric devices, etc. The ultraviolet absorption spectrum of the spider silk loaded CdS nanocomposites prepared in Example 1 for degradation of rhodamine B is shown in FIG. Figure 6 As shown; the photocurrent data of spider silk loaded CdS / NiS nanocomposites prepared in Examples 5 and 7 are as follows Figure 7 As shown, the data of photocatalytic water decomposition and hydrogen production by spider silk loaded CdS / NiS nanocomposites prepared in Examples 5 to 8 are as follows Figure 8 shown.
[0092] The present invention uses spider silk to load CdS or CdS / NiS, fully utilizing the unique fishing net structure of spider silk and the structural characteristics of silk protein, so that CdS grows in situ on its surface, increases the tightness of interface contact, improves the dispersibility of CdS or CdS / NiS nanoparticles, reduces the chance of agglomeration of nanoparticles, increases the specific surface area of the nanocomposite material, and effectively improves its photocatalytic performance; at the same time, the composite of spider silk and CdS or CdS / NiS changes the motion trajectory of photogenerated electron holes, effectively prevents the re-combination of photogenerated electrons and holes, and improves its photoelectric performance. In addition, spider silk has the characteristic of easy sedimentation, so that the composite material has the characteristic of convenient recycling.
[0093] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0094] The above are only preferred embodiments of the present invention. The protection scope of the present invention is not limited to the above embodiments. All technical solutions under the concept of the present invention belong to the protection scope of the present invention. It should be pointed out that for ordinary technicians in this technical field, some improvements and modifications without departing from the principle of the present invention should be regarded as the protection scope of the present invention.
Claims
1. A spider silk-loaded sulfide hollow nanotube composite material, characterized in that: The spider silk loaded CdS nanocomposite material with a nanotube structure is obtained by in-situ growth of CdS on spider silk; the method for in-situ growth of CdS on spider silk is as follows: adding an aqueous solution of cadmium acetate and thiourea to a spider silk solution, and heating to in-situ grow CdS on the spider silk; Alternatively, a spider silk loaded CdS / NiS nanocomposite material having a nanotube structure is obtained by in-situ growing CdS on spider silk and then loading NiS thereon; the method of in-situ growing CdS on spider silk and then loading NiS thereon is as follows: dispersing spider silk loaded with CdS in an aqueous solution of nickel acetate and thiourea, and heating to load NiS thereon; The specific preparation method of the spider silk solution is: disperse spider silk in N-methylpyrrolidone or dimethyl sulfoxide, control the temperature to 160-180°C, stir for 24 hours, then filter with a 400-mesh sieve, adjust the pH of the solution to 5-9, and obtain the spider silk solution.
2. The method for preparing the spider silk-loaded sulfide hollow nanotube composite material according to claim 1, characterized in that: The method for preparing the spider silk-loaded CdS nanocomposite material comprises the following steps: S1.1, dissolve cadmium acetate and thiourea in deionized water and sonicate the solution to completely dissolve the sulfide; S1.2, adding spider silk solution to the solution obtained in S1.1, and ultrasonically vibrating; S1.3, transferring the solution obtained in S1.2 into a polytetrafluoroethylene reactor for heating and reaction, and after the reaction is completed, centrifuging, washing, and drying the solution to obtain the spider silk-loaded CdS nanocomposite material; The method for preparing the spider silk-loaded CdS / NiS nanocomposite material comprises the following steps: S2.
1. Dissolve cadmium acetate and thiourea in deionized water and sonicate the solution to completely dissolve the sulfide; S2.2, adding the spider silk solution to the solution obtained in S2.1, and subjecting to ultrasonic vibration; S2.3, transferring the solution obtained in S2.2 into a polytetrafluoroethylene reactor for heating and reaction, and after the reaction is completed, centrifuging, washing, and drying the solution to obtain spider silk-loaded CdS hollow nanotubes; S2.
4. Evenly disperse the spider silk-loaded CdS hollow nanotubes obtained in S2.3 into an aqueous solution of nickel acetate and thiourea, and then transfer the solution into a polytetrafluoroethylene reactor for heating and reaction. After the reaction, centrifuge, wash, and dry the solution to obtain the spider silk-loaded CdS / NiS nanocomposite material.
3. The method for preparing the spider silk-loaded sulfide hollow nanotube composite material according to claim 2, characterized in that: in, In S1.1 and S2.1, the mass ratio of cadmium acetate to thiourea is 0.234:0.152-0.
182.
4. The method for preparing the spider silk-loaded sulfide hollow nanotube composite material according to claim 2, characterized in that: in, In S1.3 and S2.3, the heating temperature is 150-200° C. and the heating time is 24 h.
5. The method for preparing the spider silk-loaded sulfide hollow nanotube composite material according to claim 2, characterized in that: in, In S2.4, the mass ratio of nickel acetate to thiourea is 0.015-0.088: 0.018-0.
076.
6. The method for preparing the spider silk-loaded sulfide hollow nanotube composite material according to claim 2, characterized in that: in, In the S2.4, the heating temperature is 70-90° C. and the heating time is 12 h.
7. Use of the spider silk-loaded sulfide hollow nanotube composite material as claimed in claim 1 in photocatalytic degradation of water pollution, photocatalytic water splitting to produce hydrogen, reduction of carbon dioxide and photoelectric devices.
Citation Information
Patent Citations
Process for preparing nm semiconductor particles reinforced silk fiber base composite material
CN101008150A
Electrostatic spinning method and electrostatic spinning device for preparing nano fiber with one-dimensional order structure
CN102181948A
Preparation method and application of nano-particle functionalized artificial spider silk
CN113718520A